Pixantrone in patients with relapsed/refractory diffuse large B‐cell lymphoma: A real‐life, retrospective, multicenter trial on behalf of the "RTL" (Regional Tuscan Lymphoma network). (30th January 2022) - Cencini, Emanuele; Mecacci, Bianca; Rocco, Melania; Innocenti, Fabio; Ghio, Francesco; Puccini, Benedetta; Della Seta, Roberta; Simonetti, Federico; Mannelli, Lara; Cuccaro, Annarosa; Bocchia, Monica; Fabbri, Alberto
Abstract: Introduction: Pixantrone is a novel aza‐anthracenedione with antineoplastic activity, currently approved for multiply relapsed/refractory diffuse large B‐cell lymphoma (DLBCL), even if real‐life data are limited. Methods: We investigated pixantrone efficacy and safety in clinical practice, as 3 rd or 4 th line therapy. We retrospectively analyzed a cohort of 37 R/R DLBCL patients managed in 8 Tuscan onco‐hematological centers. Pixantrone, 50 mg/m 2, was administered on days 1, 8, 15 of a 28 days cycle for up to 6 cycles. Response to therapy was evaluated according to the Lugano 2014 classification. Results: Pixantrone was administered as 3 rd or 4 th line in 24/37 (64.9%) and 13/37 (35.1%) cases. Overall response rate and CR rate were 43.2% and 32.4%. After a median follow‐up of 6 months, 17/37 patients (46%) were alive, the main cause of death was progressive disease (14/37 cases, 37.9%). Median PFS was 3 months, median DOR was 17.9 months, and median OS was 9.7 months. A significant proportion of patients achieved a long‐lasting response >12 months (8/37 cases). IPI>2 showed a trend toward inferior PFS. Conclusion: In this real‐life setting, pixantrone demonstrated appreciable efficacy in a population with poor prognosis; in a small proportion of cases, it can be associated with long‐term remission.